A survey on big data: an emerging imparity and revolution in digital world. Issue 2 (5th November 2019) - Mukherjee, Anupam; De, Sourav; Bhattacharyya, Siddhartha
Size of the heterogeneous data is increasing rapidly at an electrifying speed. But we cannot handle this massive amount of unstructured data in traditional database, most of the data in the digital universe is unstructured. Big data analytics provides better computational power and efficient mechanism to handle this situation. This paper attempts to offer a survey report of big data, which changes rapidly of high volume, velocity, verity. In this paper we discuss some of the major challenges with a focus on big data characteristics followed by a conceptual framework of big data. This survey paper also focuses on the complexity of medical images and data mining problems.